Analisis Penawaran Cabai Rawit (Capsicum frutscens L.) di Kabupaten Boyolali - Mira Aprilliani; Ernoiz Antriyandarti; Wiwit Rahayu (MediaTrend, 2020)
The study aims to determine chili pepper’s supplies factors, the dominant factors, the elasticity of supply and disaster mitigation by farmers around the slopes of Mount Merapi in Boyolali District. The research was located in Boyolali District. Multiple linear regression is applied to analyze the data. The result shows that the amount of chili pepper production, the price of chili pepper, the price of red chili and the harvested area have significant effect on supply of chili pepper while the variable price of ZA fertilizer and rainfall are not significant. The variable of harvested area is the dominant factor in the supply of chili pepper. The elasticity of supply for the amount of chili pepper production, the price of chili pepper and red chili both in short and long term are inelastic, because the value of elasticity are less than 1. Meanwhile the variable of harvested area is elastic, because the value of elasticity in the short term and long term are 1,024 and 1,166. There is no disaster mitigation carried out by the farmers if volcano eruption of Mount Merapi occurs.